Psychometric profile of Malaysian version of the Depressive, Anxiety and Stress Scale 42-item (DASS-42) - Musa, Ramli; Sarkarsi, Rosnani; Abdul Rahim, Aidil Faszrul (Malaysian Journal of Psychiatry, 2012)
Background: The Malay short version of Depressive Anxiety and Stress Scale (DASS-21) has been widely used as a tool to measure psychological parameters in studies in Malaysia. The version has been found to be reliable for clinical and non-clinical populations. Objectives: To analyse and establish the psychometric properties of the Malay version of the DASS 42-item (BM DASS-42) among medical students. Methods: Concurrent forward and backward translations of original English DASS-42 were completed. Construct validity of the DASS-42 was established by looking at its exploratory factor analysis. Malay DASS-42 and Malay HADS were administered to a total of 411 medical students. Results: Reliability of DASS- 42 revealed excellent Cronbach’s alpha values of 0.94, 0.90 and 0.87 for depressive, anxiety and stress domains respectively. Construct validity yielded 38 items out of 42 items (90%) had good factor loadings of 0.4 and more. DASS and HADS were strongly correlated for both anxiety (r=0.87) and depression (r=0.68) domains. Conclusions: The BM DASS-42 had admirable psychometric properties among the tested population. Further studies are needed to verify these preliminary outcomes in other Malaysian subjects.